PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KOMITMEN ORGANISASI DAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris Satker di Wilayah Pembayaran KPPN Klaten yang Membawahi Kabupaten Boyolali dan Kabupaten Klaten) - Sofyan Rahma Hanafi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
The present study aims to examine the budgetary participation and performance relationship in a public sector organization. It also attempts to examine whether organization commitment and perception of innovation mediate the budgetary participation and performance relationship.To collect data of this study, survey questionnaires are used. From 150 questionnaires were given to managers in a public sector organization, questionnaires with complete answers were 89 questionnaires (59,3%). This research used Path Analysis with IBM SPSS v20 to process data.The analysis results indicate that budgetary participation and managerial performance have positive relationship and statistically significant. Budgetary participation also directly affects organization commitment and perception of innovation. But budgetary participation did not indirectly affect managerial performance via the intervening variables of organization commitment and perception of innovation.